Molecular variation in the major outer membrane protein P5 gene of nonencapsulated Haemophilus influenzae during chronic infections. - Duim, B (1997)
During the course of persistent infections by nonencapsulated Haemophilus influenzae in patients with chronic bronchitis, the major outer membrane protein (MOMP) P5 varies in molecular weight. The nature of this variability was determined by DNA sequence analysis of the P5 gene from five different H. influenzae strains and their seven MOMP P5 variants which were isolated from patients with chronic infections of the lower respiratory tract. Analysis of the P5 sequence data from the different strains revealed four well-defined, heterogeneous regions. These regions of variable sequence appeared to correspond to the regions of the gene encoding the putative surface-exposed loops of MOMP P5. The MOMP P5 variants with alterations in MOMP P5 were shown to result from DNA point mutations and codon deletions. In addition, in three variants derived sequentially from one H. influenzae strain, a frameshift mutation resulted in the formation of a stop codon in the region encoding the signal sequence of the MOMP P5 gene. Strikingly, all nucleotide substitutions in the MOMP P5 loop regions of variants were nonsynonymous, suggesting that variants with alterated amino acid compositions of the surface-exposed parts of MOMP P5 obtained a selective advantage during persistence of the infection by nonencapsulated H. influenzae in chronic bronchitis patients.